Depolarization (QRS complex) or ventricular repolarization (QT interval): Which one adds further value to diagnosis and prognosis in different clinical scenarios? - Elibet Chávez González (CorSalud, 2018)
Depolarization (QRS complex) or ventricular repolarization (QT interval): Which one adds further value to diagnosis and prognosis in different clinical scenarios?